Properties of paper from Oil Palm Fronds (OPF) by using kraft pulping process - Buang, Noradila; Mohd Yusof, Suraya; Abdullah, Nor Afifah (2012)
This research was done by using oil palm fronds (Elaeis guineensis) to study the strength properties of paper and the suitability of using oil palm frond fiber. The method that had to be used to produce paper is by using kraft pulping process with different revolution of beating that are 0 beating, 1000 beating, 2000 beating. The paper structure, physical and mechanical like tensile strength, tearing strength, and bursting strength will be tested. From the different of beating revolution, 1000 of beating revolution produced the higher strength of paper because at this level the fibre have reach it optimum point of length. From here, we can indicate that by using different level of beating revolution, it will produce the different level of paper strength.